Iota-carragenana da alga marinha vermelha Solieria filiformis versus iota-carragenana comercial: propriedades estruturais e reológicas - Holanda, Márjory Lima (2007)
Marine red algae are an abundant source of carrageenans, a generic name for a family of polysaccharides, obtained by extraction from certain species of red seaweeds (Rhodophyta). Carrageenans represent one of the major texturising ingredients in the food industry. The quantitative and rheological analysis of carrageenan batches are of greatest importance for both ingredient suppliers and food industries to deliver a constant consumer product and to develop new applications based on their unique intrinsic properties. The red marine alga Solieria filiformis was submitted to aqueous extraction of your polysaccharides and presented a yield de 1.4% in the extraction to cold (Sf-25), 98.2% at 90°C (Sf-90) e 0.4% at 120°C (Sf-120). A comercial t-carrageenan (1.-CAR) was utilized to compere the chemical and rheological characteristics of the Sf-90. The sulfate, protein and carbohydrates contents in the Sf-90 and L-CAR were 32.2, 5.5 and 61.7% and 31.4, 0.3 and 50.3%, respectively. In general, the FTIR spectra of Sf-90 e L-CAR were similar and typical absorption peaks were present at 1250 cm-1 (ester sulfate), 930 cm-1 (3,6-anhydro-galactose), 850 cm-' (D-galactose-4-sulfate) and 805 cm-1 from 3,6-anhydro-galactose-2-sulfate (DA2S). The 130 RMN spectra of Sf-90 and i-CAR also showed anomeric signals corresponding at chemical structure of a l-carrageenan, constituted mainly of G4S (51.9 and 57.1%, respectively) and DA2S (48.1 and 42.9%, respectively). However, the 'H RMN spectrum of Sf-90 presented an intense signal at 3.41 ppm corresponding to substitutions in C-6 of G4S for groups 0- methyl, small amounts of x -carrageenan and precursors of i-carrageenan. The samples Sf-90 and -CAR were desulfated and your spectra of HMQC confirmed your sulfate patterns. Sf-90 presented mass molar medium of 590.000 gmol-1 while i-CAR presented mass molar superior average (2.100.000 gmol-1). Experiments to avaliate the rheological behaviors of Sf-90 and i-CAR were performed in duplicate. The power law and Herschel-Bulkey models fitted most of the experimental results. Sf-90 1% (at 25°C) was exception, characterized by a yield stress and hence the rheograms were fitted with the Herschel-Bulkley model. Furthermore, i-CAR showed a Newtonian behavior at 0.1%. Arrhenius model was used to describe the temperature effect. Sf-90 0.5% showed a hight temperature dependency (Ea = 117, 31 kJmol-1). The presence of Sf-90 in milk resulted in synergy manifested as enhancements in viscosity suggesting interation carrageenan/protein. True gels with presence of hysteresis were formed by Sf-90 at concentrations 1, 2 and 3% while i-CAR formed weak gels just in the concetration of 3%. Therefore, based on the very similar quimical structure and rheological behavior of Sf-90 e i-CAR, the alga S. filiformis can be harvested and addressed to the industrial extraction processes without any previous sorting